Intra muscular hemangioma of masseter: A rare case scenario - Kandasamy Murugan; E Gracelin Ranjitha; D Angeline Deepthi; Chinnappa Saravana Bharathi (Wolters Kluwer Medknow Publications, 2018)
Intramuscular hemangioma (IMH) is a rare congenital benign vascular tumour occuring in the skeletal muscles. Mostly they occur in the muscles of lower extremity and rarely in the muscles of oral cavity. This is a case report of a 37 year old female patient with a Chief complaint of painless dependent swelling in the left middle third of the cheek region for the past 4 years. Clinical examination supported by the findings of Ultrasonography [USG] and Magnetic resonance imaging [MRI] leading to the diagnosis of intramuscular hemangioma of masseter. The diagnosis is later confirmed after Excisional biopsy followed by histopathologic evalution of the biopsied section. The masseter muscle is most frequent muscle accounting for 5% of all intramuscular hemangiomas. Due to the fibro vascular nature IMH have a rubbery, firm texture and vascular bruits or thrills are infrequent. The management has ranged from steroids to injection of sclerosing agents, radiation therapy, and surgical excision.